ANALYSIS OF THE INFLUENCE OF CELEBRITY ENDORSEMENT ON GENERATION Z'S PURCHASE DECISIONS FOR COSMETIC PRODUCTS IN INDONESIA - Syahrul, Khaidir (Nusantara Economics and Entrepreneurships Journals, 2025)
Trend Celebrity endorsement is a dynamic phenomenon in marketing that reflects changes in consumer behavior, especially Generation Z. The purpose of this study is to describe the influence of celebrity endorsement on cosmetic product purchasing decisions in Indonesia. This study uses a library method. The results of this study can be concluded as follows: 1) Celebrity endorsement has a significant influence on cosmetic product purchasing decisions in Generation Z, which is influenced by the credibility of the celebrity; 2) Factors that influence the effectiveness of endorsement include consumer perception of the product, content visualization, consumer attention, personal characteristics of the celebrity (credibility, charisma, relevance), situational factors, content quality, and engagement rate; 3) The impact of celebrity endorsement is an increase in purchasing interest and changes in purchasing behavior in Generation Z; 4) Implications for cosmetic brands are the importance of choosing celebrities that match the target market, creating interesting and relevant content, and increasing interaction with the audience.